Key determinants to school breakfast program implementation in Philadelphia public schools: Implications for the role of SNAP-Ed - Fornaro, Elisabeth G.; McCrossan, Erin; Hawes, Peter; Erdem, Ebru; McLoughlin, Gabriella Maria (Frontiers in Public Health, 2022)
Background Policies addressing food insecurity are only effective if they are implemented successfully, serving those most at risk. Universal school meals provide a key intervention to schools that serve predominantly low-income families by providing free school breakfast and lunch to all. Unfortunately, low uptake of such provisions among students is concerning especially regarding school breakfast, warranting key implementation support for schools to ensure student nutrition needs are met. Thus, the purpose of this study was to evaluate the determinants of implementing two different school breakfast programs and pragmatic strategies for serving breakfast in ways that maximize student participation. Methods A qualitative study was conducted between 2018 and 2020 within the School District of Philadelphia (SDP) comprising surveys, interviews, and observations to assess contextual determinants of two distinctive breakfast models: Breakfast in the Classroom (BIC) and Cafeteria after the Bell (CAB). Principals and lead kitchen staff completed surveys to assess determinants of breakfast model adoption. Principals, lead kitchen staff, classroom teachers, climate (i.e., social emotional wellbeing), and facilities staff subsequently participated in interviews to discuss implementation determinants (i.e., facilitators and challenges) and strategies for maximizing student participation. Observations provided rich data to triangulate interviews and survey data. Survey data were analyzed using frequency analysis, and observation and interview data were analyzed through thematic analysis. Presentation of themes was framed by the Consolidated Framework for Implementation Research. Results Results highlighted several positive determinants to participation including addressing student and family needs, making data-informed decisions, and providing hot meals and fruit based on student tastes. Negative determinants to implementation comprised challenges to SNAP-Ed-funded policy changes to promote student breakfast participation, lack of communication between administration, and staff and turnover among food service staff. Strategies included modifying school entrance procedures and combining breakfast with other education-related tasks to minimize instructional time lost through breakfast after the bell schedules. Discussion Data highlight the need to include implementation partner expertise when designing interventions for increasing reach and effectiveness of school meal programs. Future research that directly tests implementation strategies and key outcomes of reach/participation, among others, is critical to bridging the policy to practice gap in school nutrition programs.